Corruption, Social Infrastructure and their Role in Shaping Sustainable Development - Zaitoun, Noha Mahmoud Ashraf Moamed Ali (The Arab Journal of Administration, 2024)
This paper aims at studying the impact of corruption, as one of the most important features that shape a country’s social infrastructure, on sustainable development, within the framework of institutional quality (good governance). In order to overcome the problem of the omitted variable bias, an extensive research was carried out into the possibility that corruption could boost economic efficiency at the country level. In other words, the study investigates whether or not the “Greasing the wheels” hypothesis is actually realized in the relationship between corruption and sustainable development. Using three different approaches, deducted from previous studies and based on the “fixed effects” and the “dynamic Panel data” methods, the study concluded that a good social infrastructure, including efficient institutions and policies, is considered one of the main pillars for achieving sustainable development. It was also found that transparency and low corruption levels represent crucial factors for shaping social infrastructure and raising the level of sustainable development. In contrast to those robust results, mixed evidence was found about the extent of the “Greasing the wheels” hypothesis validity, although most findings supported the inability of corruption to boost economic efficiency.